CORINTH IN THE OTTOMAN PERIOD (1458-1687 AND 1715-1821) THE AFTERLIFE OF A GREAT ANCIENT GREEK AND ROMAN METROPOLIS - Machiel KIEL (Fayoum University, 2016)
Corinth, known to the Ottomans as Korintos or Koritos, later as Gördüs, was in Antiquity a sea port and one of the largest and most famous cities of ancient Greece. The Ottoman name Gördüs - used from the second half of the sixteenth century onwards - derives from the local, dialectical pronunciation “Gortho”. Throughout the Greco-Roman Antiquity it was one of the largest cities of the Eastern Mediterranean. In the late Byzantino-Frankish period, Corinth sunk to the level of 50 decrepit houses, as reported by the Italian notary Niccolo da Martoni from Capua in 1396 A.D. In Ottoman times (1458-1687 A.D and 1715-1822A.D) the town was an important fortress (the “Key of the Morea”, at first the seat of the Ottoman SandjakBey of the Morea and centre of a large Kadılık (district under the supervision of a Kadı/Judge). Later, especially in the eighteenth century, it developed into a Muslim center of local importance, containing a number of monumental domed mosques, some colleges of higher Islamic learning (medrese) and a number of dervish convents (tekke). Among the latter was the Tekke of the Gülşeniye Order of dervishes which owes its existence to the work of the poet and writer HasanSezâ'i, a native of Corinth, and his son and successor MehmedSadıkEfendi. After a series of destructive earthquakes, especially that of 1858 A.D, the destroyed city was rebuilt on a new site on the shores of the Gulf of Corinth, seven km to the north-east of the old city. The site of the old city and medieval Byzantine/Frankish and Ottoman settlement survived as the village of Palaio Korinthos. The history of Corinth as an Ottoman town has never been told with any detail and the available Ottoman source material was hardly, or never, used.